Respostas
respondido por:
12
f(x) = ax + b
f(2) = 2a + b = 5 .(-1)
f(3) = 3a + b = -5
-2a - b=5
3a + b=5
------------------
a = 10
3a+b = 5
3.10 + b = 5
30 + b = 5
b = 5 - 30
b = -25
F(4)=10.4-25
F(4)=40-25
F(4)=15
EduardaBöesing:
Na multiplicação (-1) o 5 não seria negativo?
respondido por:
1
Resposta:
f(x)= ax +b
f(3)= a.3 +b
5= 3a +b
f(-2)= a.(-2)+b
- 5 = -2a +b
3a + b = 5
- 2a + b = -5(×-1)
3a +b =5
2a -b = 5
_______+
5a = 10
a=10/5
a= 2
3a + b =5
3.2 + b =5
6+b = 5
b= 5-6
b= - 1
f(x) = ax + b
f(x)= 2 x - 1
f(7)= 2.7 -1
f(7)= 14 - 1
f(7)= 13
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás